Health education in adherence to treatment for diabetic patients - Rumão Batista Nunes de Carvalho, Zálya Lidiane Cavalcante de Deus, Juliana Gonçalves da Silva, Ana Roberta Vilarouca da Silva, Gerdane Celene Nunes Carvalho (Revista de Enfermagem da UFPI)
DOI: https://doi.org/10.26694/reufpi.v2i3.1097